2016
DOI: 10.1308/rcsann.2016.0125
|View full text |Cite
|
Sign up to set email alerts
|

Day case laparoscopic cholecystectomy in patients with high BMI: Experience from a UK centre

Abstract: INTRODUCTION Symptomatic gall stones may require laparoscopic cholecystectomy (LC), which is one of the most commonly performed general surgical operations in the western world. Patients with a high body mass index (BMI) are at increased risk of having gall stones, and are often considered at high risk of surgical complications due to their increased BMI. We believe that day case surgery could nevertheless have significant benefits in terms of potential cost savings and patient satisfaction in this population.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 32 publications
2
13
1
2
Order By: Relevance
“…Our results showed that age was not associated with a longer hospital stay. In addition, our results also showed that gender, BMI [ 23 , 24 ], previous upper intra-abdominal surgery history, surgeons' status, thickened gallbladder wall, and the presence of adhesions were not associated with delayed hospital stay.…”
Section: Discussionsupporting
confidence: 58%
“…Our results showed that age was not associated with a longer hospital stay. In addition, our results also showed that gender, BMI [ 23 , 24 ], previous upper intra-abdominal surgery history, surgeons' status, thickened gallbladder wall, and the presence of adhesions were not associated with delayed hospital stay.…”
Section: Discussionsupporting
confidence: 58%
“…With regard to the Body Mass Index, a study conducted in the United Kingdom, which included patients with obesity and morbid obesity submitted to outpatient videolaparoscopic cholecystectomy (n=571), found an increase in the Body Mass Index associated with an increase in the infection rate (16) , which differs from this study, as there was no association.…”
Section: Discussioncontrasting
confidence: 99%
“…Figure 1 shows the modified PRISMA flowchart for identification and inclusion of relevant papers. Twentythree studies were excluded from the meta-analysis; 10 papers were deemed low quality [53][54][55][56][57][58][59][60][61] and 13 papers did not provide readmission rates specific to LC [62][63][64][65][66][67][68][69][70][71][72][73][74].…”
Section: Resultsmentioning
confidence: 99%